The Influence Of Brand Image And Product Quality On Consumer Loyalty: A Study On Daviena Skincare Users Among FEBI UIN Jurai Siwo Lampung Students - Neni Rahmawati; Hanna Hilyati Aulia (Nuban Jagadhita Centre, 2026)
Purpose: The rapid growth of the skincare industry in Indonesia has intensified competition among local and international brands, making consumer loyalty an important factor for business sustainability. Daviena Skincare, a local skincare brand, has gained significant popularity among young consumers, particularly university students. This study aims to examine the influence of brand image and product quality on consumer loyalty among users of Daviena Skincare in the Faculty of Economics and Islamic Business FEBI UIN Jurai Siwo Lampung. Methodology: A quantitative approach was employed using a survey method. Data were collected from 51 respondents selected through proportional random sampling and analyzed using multiple linear regression. Findings: The findings reveal that brand image has a positive and significant effect on consumer loyalty, while product quality also has a positive and significant influence. Simultaneously, both variables significantly affect consumer loyalty. The coefficient of determination (R²) indicates that 62.7% of consumer loyalty can be explained by brand image and product quality, whereas the remaining 37.3% is influenced by other factors outside the scope of this study. These findings suggest that strengthening brand reputation and maintaining product quality are essential strategies for enhancing customer loyalty in the skincare industry.